Functional foods from the dietetic perspective - Fatimah Arshad (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2002)
Foods and beverages, which are beneficial to health, are referred to as functional foods. In Malaysia, the definition of functional food is still inconclusive. However, direct selling outlets throughout the nation is flooded with these food items since they are distributed under the food supplement category and not covered by the Food and Drug Act 1983. In trying to control the quality and safety of these products, the Ministry of Health of Malaysia has assigned three bodies to participate in the implementation of laws for functional foods. The three bodies are the Department of Food Quality, Malaysian National Codex Committee and The National Pharmaceutical Bureau. The area of neutraceuticals and functional food is still under active research and justifications. As scientists, dietitian require, results from clinical trials before health claims can be made regarding a particular product. The issue of dose and strength of the food component used for therapy is also questionable. Currently we have to protect the consumers on false claims and high costs made by direct sellers. At the same time we have to be more assertive promoting healthy eating and lifestyle campaigns to educate the public. Malaysia has officially launched and implemented its dietary guidelines. However, functional food claims are not incorporated in the guidelines. It is implicit to encourage the consumption of many functional food ingredients such as dietary fibers, antioxidants, carotenoids, phytochemicals, vitamins and minerals. At the same time we should curb the consumption of too much fat, sugar, salt and alcohol in our goal towards the promotion of health. Concurrently, it must be highlighted that there is no one single health food. The key issue is variety based on our food pyramid. Other risk factors such as family history, gender, age, smoking, inactivity, stress aside from high fat, cholesterol, salt, sugar and low fiber intake will have to be incorporated in the maintenance of health. As nutritionists and dietitians, we do not advocate the act of popping pills or tablets or other forms of therapy since it is costly and an unhealthy way of ensuring health. We advocate healthy eating via natural foods and ingredients and the practice of healthy lifestyle.